Estudo da degradação e propriedades físico-químicas do extrato aquoso da casca de laranja das espécies Citrus sinensis e Citrus aurantium - Spode, Emanueli Fernanda (2020)
Orange is one of the most consumed fruits worldwide, either in its fresh form or after its processing in the form of concentrated juices or pulps. As a secondary product of the processing of oranges, its essential oil is obtained, which is a mixture of compounds with high added value and with several applications in the pharmaceutical, cosmetics and food industries. The oil is obtained through the cold pressing method and the aqueous extract can be obtained by the hydrodistilation process. This extract was extracted from the pericarp of the species Citrus sinensis by the hydrodistillation process in which was obtained an average yield of 1.32%. The pre-treatment of the vegetable matrix with cellulase and hemicellulase obtained from T. reesi and A. niger resulted in an increase in oil yield of more than 50% in average. The extract obtained was analyzed by GC/MS for qualification and quantification of the chemical constituents. It was found that R-limonene was the major constituent in all samples (> 90%). The photodegradation of the extracts was evaluated by analysis in the UV-Vis region and by gas chromatography and the results showed that the aqueous extract is unstable and susceptible to degradation when exposed to adverse conditions. The antimicrobial activity of the extracts obtained against the microorganisms E. coli, B. subtilis and S. aureus was evaluated, and it was verified that all showed moderate activity. Regarding the antioxidant activity, a new evaluation method based on the sequestration of hydrogen peroxide could be proposed and the results corroborate those already found by widely used methods, such as DPPH and the β-carotene / linoleic acid cooxidation method,for orange essential oil, classifying the aqueous extracts of the oil as weak antioxidant agents. The toxicological effects of the oil extract, such as LD50, MRTD, absorption rate and excretion were evaluated and it was concluded that they are safe extracts to use, since the most toxic components are present in very low concentration, and it would take a very large amount of daily oil consumption to see any harm from its use.